BUDAYA JAWA DALAM NOVEL MARS KARYA AISHWORO ANG: TINJAUAN ANTROPOLOGI SASTRA - Dian Nathalia Inda (Kantor Bahasa Provinsi Gorontalo, 2017)
This research aimed to describe the variety of Javanese culture that contained in novel Mars by using the theory of literary anthropology. The source of data was novel Mars.The purpose of this paper is to describe the Javanese cultures on novel Mars. Data were analyzed using descriptive-qualitative method with literature review technique. The results of the analysis showed the diversity of Javanese culture that exists in the novel of Mars in the form of traditions and customs, arts, traditional buildings, religions, and traditional beliefs. Javanese culture has been eroded, but some are still routinely held every year.